Slovak Republic : Insolvency and Creditor Rights Systems - World Bank (Washington, DC, 2013)
The assessment team interviewed a cross section of country stakeholders regarding the effectiveness of the legal infrastructure, and its implementation supporting debtor-creditor relationships, corporate insolvency and credit risk management, and resolution practices, including among others, members of the Inter-Agency Commission for the preparation of a new insolvency law, and members of the drafting team for the new collateral law; and, various professionals serving as trustees, executors, lawyers and accountants also provided their input. The conclusions in this assessment are based largely on the above interviews, a review of applicable legislation, data and information, various reports prepared by the Bank between 1999-2001, and other reports or analyses pertaining to the areas assessed, including the project on the new collateral legislation, and registration system for pledges (charges). Some laws unavailable in English at the time were discussed in a number of meetings with institutions, and professionals in the public, and private sectors, and, translations have been requested for follow-up. In addition, at least three commercial banks provided responses to a questionnaire pertaining to credit risk management, and corporate recovery practices with respect to distressed assets. Policy recommendations on Creditors' rights and enforcement procedures need development as follows: rules or legislation on sufficiency of security/transfer/ownership documents should be promulgated to remove the discretion of the land registry, and prevent delay of transactions due to refusals of district land registry offices to register documents; auction procedures should be refined to allow for more realistic minimum bids, more transparent and corruption-resistant procedures, and less court involvement; debtor mechanisms for delaying enforcement of their creditors' rights should be reduced, and in many cases eliminated. Debtor's rights can be protected through summary proceedings, in a different forum dedicated to routine debt enforcement; and, enforcement of first, but not final judgments should be allowed subject to posting of appropriate bond. In addition; the Bankruptcy Law should be further amended to include mandatory deadlines, with time-bound procedures, to avoid the decimation of asset value over time. The moratorium on creditor action should be effective from the time of filing the petition, and the stay on secured creditors counter-balanced by safeguards to protect, and preserve the value of a separate creditors' interest in collateral from deteriorating in value. Creditors' committee meetings should be convened within 30 days of petition filing, and creditors' powers to supervise dealings of the trustee, should be better.